Family Function and Self-esteem among Chinese University Students with and without Grandparenting Experience: Moderating Effect of Social Support - Shi, Jingyu; Wang, Lu; Yao, Yuhong; Su, Na; Zhao, Xudong; Zhan, Chenyu (Frontiers in Psychology, 2017)
Abstract This study examines the association between family function and self-esteem of Chinese university students with grandparenting experience, and explores the moderating effects of social support in this link. 2530 university students (1372 males and 1158 females) from a Chinese university completed the Perceived Social Support Scale (PSSS), the Rosenberg’s Self-esteem Scale (SES) and the Family Assessment Device (FAD). 645 (25.69%) students reported grandparenting experience and they reported lower scores on self-esteem and social support than the students raised only by their parents. The grandparenting group scored higher on such dimensions of family functioning as Communication (CM), Role (RL), Affective Involvement (AI), Affective Responsiveness (AR) and General Family Function (GF) than their counterpart group. For both groups, self-esteem scores were positively correlated with social support scores, while negatively correlated with FAD all subscale scores. Hierarchical regression analysis showed that for the students with grandparenting experience the social support moderated the relationship between GF and self-esteem. When students reported a high level of social support, those with low GF score reported higher scores in self-esteem than those with low self-esteem. However, in case of low social support, there were no differences in self-esteem between groups with high and low GF scores. These findings suggest that social support plays a positive role to relieve the adverse impact of poor family function on self-esteem of the adolescents with grandparenting experience. In addition, the significance and limitations of the results will be discussed.